2001
DOI: 10.1089/104303401750298544
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol and Lobar Administration of a Recombinant Adenovirus to Individuals with Cystic Fibrosis. II. Transfection Efficiency in Airway Epithelium

Abstract: A phase I clinical trial was conducted in which recombinant adenovirus containing the cystic fibrosis trans-membrane regulator (CFTR) (Ad2/CFTR) was administered by bronchoscopic instillation or aerosolization to the lungs of cystic fibrosis (CF) patients. In this paper, we evaluate the efficiency of Ad2/CFTR-mediated transduction of bronchial airway cells. The ability of an Ad2/CFTR vector to transduce airway cells was first evaluated in patients to whom the vector was administered by bronchoscopic instillati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(35 citation statements)
references
References 24 publications
0
34
0
1
Order By: Relevance
“…A more recent phase I clinical trial using aerosolized lobar administration of recombinant CFTR adenovirus demonstrated by in situ hybridization that nuclear-localized vector DNA was not readily detected in small samples of epithelial brushings. However, high levels of infection occurred in mononuclear cells and squamous metaplastic epithelial cells (135). In summary, clinical trials to date with recombinant adenoviral-mediated delivery of CFTR have demonstrated low levels of transduction, likely because the apical surface of airway epithelia lacks CAR receptors.…”
Section: Recombinant Adenovirusmentioning
confidence: 95%
“…A more recent phase I clinical trial using aerosolized lobar administration of recombinant CFTR adenovirus demonstrated by in situ hybridization that nuclear-localized vector DNA was not readily detected in small samples of epithelial brushings. However, high levels of infection occurred in mononuclear cells and squamous metaplastic epithelial cells (135). In summary, clinical trials to date with recombinant adenoviral-mediated delivery of CFTR have demonstrated low levels of transduction, likely because the apical surface of airway epithelia lacks CAR receptors.…”
Section: Recombinant Adenovirusmentioning
confidence: 95%
“…NIHR Journals Library www.journalslibrary.nihr.ac.uk low, 41,42 and is associated with lung inflammation 43,44 and the development of neutralising immune responses that, to date, has precluded repeated administration. 45 AAV-based CFTR gene transfer appears less proinflammatory, 46-48 although repeated administration is also inhibited by immunological reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Use of a microsprayer device inserted through a bronchoscope does increase vector distribution through the airways, although this remains an invasive technique (Harvey et al, 1999;Cipolla et al, 2000;Beck et al, 2002). Administration of aerosolized vectors, both viral and nonviral, can result in more effective distribution throughout the lungs (Sené et al, 1995;Brown and Chowdhury, 1997;Gautam et al, 2000;Lerondel et al, 2001;Perricone et al, 2001). However, the efficiency of many aerosolization devices remains low, with a significant portion of the vector deposited in the machinery or upper airways.…”
Section: Discussionmentioning
confidence: 99%